EXPERIMENTAL STUDY OF VARIATION OF THE EFFECT OF THE PELTON TURBINE VALVE OPENING ON ELECTRICITY ENERGY THAT WAS PRODUCED TO TURNED ON A LAPTOP - Syamsuri Syamsuri; Hasan Syafik Maulana; Abdul Sulisyanto (Universitas Sultan Ageng Tirtayasa, 2018)
In this modern era all human activities are still very dependent on non-renewable energy sources. Electricity is one of the most important needs for humans, starting from lighting, communication, transportation and other needs. Energy supplies, especially fossil energy, are increasingly depleted, therefore an alternative energy source that is environmentally friendly and abundant availability is needed. One alternative energy source is water energy, especially energy derived from Piko Hydro. With variations in valve openings installed on pelton turbines of 18ᵒ, 36ᵒ, 54ᵒ, 72ᵒ, and 90ᵒ analyzed using the experimental method to determine the efficiency of the pelton turbine system used to produce electrical power from the Piko Hydro system. The results of this study indicate that the highest power is produced with a 90ᵒ faucet opening where the Power is 3.96 Watts and the system efficiency is 14.56%.